Relationship of Hedonic and Utilitarian Values and Their Influence on Consumer Satisfaction and Loyalty - Adriana CUADROS; Daniela RODRÍGUEZ; Martin A. MAURICIO (Communications of International Proceedings, 2022)
The objective of this research is to test the influence of utilitarian and hedonic values on consumer satisfaction and its relationship with loyalty. The empirical study used for the verification of the hypotheses was a quantitative type of study through a non-probabilistic sampling of 203 people who have purchased through a web page of the clothing and footwear sector in the last 6 months. The statistical processing used was SEM (Structural equation modeling) and for the analysis of the data results the PLS (Partial Least Squares) technique was used, since it allows a multivariate analysis. The study concludes that there is a relationship between utilitarian values, hedonic values, satisfaction and loyalty. An important issue to highlight is that in previous research, several authors have used different groupings for hedonic and utilitarian values, therefore, later in the research the groupings used to perform the respective analyses are listed and described. It is considered that, despite the limitations found in the research, these represent a very important value for companies and to be able to understand more accurately the customer behavior in an online environment.
Keywords: hedonic values; utilitarian values; satisfaction; loyalty.